Looking for Health or Normative Influence on Spa Consumption at Wellness Destination of Bali Indonesia: A Structural Equation Modeling Analysis - Christine PETR; I Gusti Ayu Oka Suryawardani; I Gusti Raka Purbanto (Pusat Kajian Bali Universitas Udayana, 2025)
This research investigates the influence of social norms and prior expectations on tourist satisfaction and loyalty in Bali’s wellness destinations, addressing a gap in understanding normative influence during and after consumption. The research aims to determine whether conforming to tourist norms is an autonomous source of satisfaction, independent of the spa’s intrinsic qualities or expected health benefits. Employing structural equation modeling on data from 355 international spa tourists, the research reveals that social norms have a more significant impact than expected health benefits on tourist behavior. Conformity perceptions were found to be stronger among spa lovers compared to spa discoverers. The novelty lies in its examination of compliance with social norms and personal benefit expectancies during the destination consumption phase. These findings emphasize the significance of normative influence in shaping tourist behavior at wellness destinations, offering valuable insights for marketing strategies that leverage social norms to enhance customer loyalty and destination competitiveness.